The Effects of Experiential Marketing and Store Atmosphere on Customer Loyalty of MSMEs in West Java - Madiawati, Putu Nina (Binus Business Review, 2023)
The research explored the relationship between experiential marketing, store atmosphere, customer satisfaction, and customer loyalty, as well as strategies that businesses could use to enhance these factors and improve customer loyalty. The research focused on Micro, Small, and Medium Enterprises (MSMEs) in West Java, Indonesia, which owned physical stores. The research applied a causal quantitative method. Through a thorough analysis of existing research and empirical research of 384 respondents using Structural Equation Model Partial Least Square (SEMPLS) methodology, the research provided valuable insights for MSMEs looking to increase customer loyalty and build a loyal customer base. The results show various contributions analyzing how customer loyalty is affected by experiential marketing and store atmosphere. It also implies how customer satisfaction mediates the relationships between those antecedents and customer loyalty. Providing recommendations and implications shows that the research can be a useful contribution to marketing and entrepreneurship topics. The research offers practical recommendations and implications for businesses, emphasizing the importance of implementing effective experiential marketing strategies and creating a welcoming store atmosphere to foster customer satisfaction and loyalty. By understanding the impact of these factors on customer loyalty, MSMEs can develop targeted strategies to improve customer experiences and build long-term customer relationships.